Electrodeposition of a Ni-P-Ti3C2Tx/MoS2 coating incorporating MoS2 intercalated Ti3C2Tx particles - Du, Yingchao; Wang, Dongdong; Si, Pengchao; Wei, Lianqi; Wang, Yongliang; Yu, Bo; Zhang, Xiaomeng; Ye, Shufeng (Surface & coatings technology, 2018)
As a promising material, Ti3C2Tx has received much attention in recent years for brilliant performances in conductivity and lubricity. In order to modify the property of Ti3C2Tx, MoS2 intercalated Ti3C2Tx (Ti3C2Tx/MoS2) powders are made from hydrothermal reaction, which can prohibit oxidization for MoS2 particles. Ni-P-Ti3C2Tx/MoS2 and Ni-P-Ti3C2Tx composite coatings are prepared by electroplating technique with addition of Ti3C2Tx/MoS2 and Ti3C2Tx particles, respectively. Compared to Ni-P composite coatings, Ni-P-Ti3C2Tx/MoS2 and Ni-P-Ti3C2Tx composite coatings show a decrease in coefficient of friction (COF). The wear loss of Ni-P-Ti3C2Tx/MoS2 composite coating is only about 0.10 mg after 5 min, under dry-grinding with the load of 2 N and circle radius of 1 cm. It is worth to mention that the microhardness of the two composite coatings gets improved much, which can be up to 1200 kg mm−2. Even though the surface roughness of Ni-P-Ti3C2Tx/MoS2 composite coating increases, the surface of the composite coating is converted from hydrophilic to hydrophobic. •MoS2 was successfully intercalated into Ti3C2Tx by hydrothermal reaction.•The addition of Ti3C2Tx/MoS2 converted the wettability of Ni-P composite coating.•The microhardness of Ni-P-Ti3C2Tx/MoS2 composite coating is up to 1200 kg mm−2.•The COF and wear loss of Ni-P-Ti3C2Tx/MoS2 coating show a dramatic reduction.